2021
DOI: 10.33369/diksains.1.1.10-17
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran Model Debat Aktif Pada Materi Pemanasan Global Untuk Siswa Kelas Xi Sma

Abstract: ABSTRAK Berdasarkan hasil obesrvasi yang dilakukan disekolah, perangkat pembelajaran yang digunakan guru belum tersusun dengan baik dan belum menggunakan instrumen penilaian yang sesuai dengan model pembelajran yang digunakan. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran model debat aktif pada materi pemanasan global untuk kelas XI SMA. Penelitian ini menggunakan metode penelitian research and development dengan model  Sugiyono Level 1. Adapun tahapan-tahapan yaitu potensi dan masalah, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Based on literature analysis regarding difficulties in learning global warming material, it was found that teachers still need help understanding and preparing learning tools, determining models, and lack creativity (Deka, et.al., 2020;Pradita, et.al., 2020). Meanwhile, according to students, there is no learning about global warming material in class; students are only asked to study independently (Deka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature analysis regarding difficulties in learning global warming material, it was found that teachers still need help understanding and preparing learning tools, determining models, and lack creativity (Deka, et.al., 2020;Pradita, et.al., 2020). Meanwhile, according to students, there is no learning about global warming material in class; students are only asked to study independently (Deka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%